EXPERIMENTAL RESERCH OF DYNAMIC LOADS IN THE LIFTING DRIVE OF A OVERHEAD CRANE - STRELBITSKIY, VICTOR; YAREMENKO, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Overhead cranes are widely used for   the overloading cargo in port warehouses. However, the difficult economic situation in Ukraine has led to the fact that more than 90% of cranes in ports have fulfilled the standard period, despite this they continue to be operated in the mode of intensive cyclic loading. Simultaneous replacement of reloading equipment will lead to significant costs that the state cannot afford today. Therefore, it is not worth counting on radical changes in the near future. One of the main elements of overhead cranes are lifting drives, which significantly affect their price and technological capabilities. Nevertheless, intensive operation of cranes leads to significant dynamic loads in the rope, which is the main reason for their failureThe analysis of the work showed that the dynamic loads in the lifting drive of overhead cranes with an excess service life have not been sufficiently studied. Consequently, the assessment of the level of dynamic forces in the drives of lifting machines remains an urgent scientific and applied task today.The purpose of the work is to experimentally study dynamic loads in the lifting drive ropes of a double-girder overhead crane with a lifting capacity of 15 tons, taking into account the specifics of the work.  The objects of research were 2 identical double-girder overhead cranes with a lifting capacity of 15 tons, which worked for more than 20 years in open-type warehouses of the port reloading cargo from semi-wagons. The experiments were divided into two series, conducted with loads weighing 5 tons, 10 tons and 15 tons. the load with the same weight was lifted three times, the results were averaged.As a result of the conducted studies, it was found that the change in the force of the rope branches over time has an oscillatory character, depends on the weight and lifting mode of the load, and reach the limit values when lifting the load in the "pick-up"mode. With the same weight of the load, the dynamic forces in the rope in the lifting mode with "picking up" exceed 1.05....1.1 times the effort from the "weight", which is quite consistent with the known research results. The dependence of the forces in the rope on the weight of the load is nonlinear.
Keywords: overhead crane; lifting mechanism; rope; dynamic loads; dynamism coefficient